2009
DOI: 10.1186/1475-2875-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical stability of expired fixed dose combination artemether-lumefantrine in uncontrolled tropical conditions

Abstract: Background: New artemisinin combination therapies pose difficulties of implementation in developing and tropical settings because they have a short shelf-life (two years) relative to the medicines they replace. This limits the reliability and cost of treatment, and the acceptability of this treatment to health care workers. A multi-pronged investigation was made into the chemical and physical stability of fixed dose combination artemether-lumefantrine (FDC-ALU) stored under heterogeneous, uncontrolled African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Statistical analysis proved that the method is repeatable and selective for the analysis of artemether as bulk drug and in pharmaceutical formulations. Our findings is consistent with the results of Bate et al [25] who found that though artemetherlumefantrine has passed its labelled expiry date with about 3months, their concentration was stable and not degraded and also agrees with Arun and Smith [26] who developed and validated a HPLC-UV method for the simultaneous estimation of artemether and lumefantrine in fixed-dose combination tablets. In their study, HPLC analyses were carried out with a coupled UV detector.…”
Section: Resultssupporting
confidence: 82%
“…Statistical analysis proved that the method is repeatable and selective for the analysis of artemether as bulk drug and in pharmaceutical formulations. Our findings is consistent with the results of Bate et al [25] who found that though artemetherlumefantrine has passed its labelled expiry date with about 3months, their concentration was stable and not degraded and also agrees with Arun and Smith [26] who developed and validated a HPLC-UV method for the simultaneous estimation of artemether and lumefantrine in fixed-dose combination tablets. In their study, HPLC analyses were carried out with a coupled UV detector.…”
Section: Resultssupporting
confidence: 82%
“…Most recent data indicate that AL tablets may be chemically and physically stable well beyond the stated shelf-life even under tropical, ie, warm, conditions 44. These data should, however, not pave the way for a permissive attitude about the stability of AL tablets, but rather lead to thorough investigation and examinations and, if possible, chemical and galenic improvement.…”
Section: Procurement Of Artemether–lumefantrine By Whomentioning
confidence: 99%
“…Drug quality and stability in the developing world is a serious concern. Although there have been some studies of artemisinin quality and stability [ 9 11 ], this study appears to be the first peer-reviewed study to both evaluate the products’ quality and then study its stability under ambient tropical conditions. The study products were also compared to a reference product.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by MS and NMR revealed an artesunate degradation product that was virtually undetectable in the non heat-stressed samples. Bate et al obtained samples of artemether-lumefantrine that were 1 – 58 months past their labelled expiry date [ 11 ]. They found that 97% of expired products passed tests for tablet integrity and the presence and amount of active ingredients using thin layer chromatography, tablet disintegration and infrared (IR) spectroscopy but they did not study the samples using dissolution testing.…”
Section: Introductionmentioning
confidence: 99%